Associations of Dietary Live Microbes Intake and Prevalence of Prediabetes in US Adults: A Cross-Sectional Analysis - Ge X; Du J; Wang J; Xi L; Gao J; Zhou P; Peng W; Huang S (Journal of Multidisciplinary Healthcare)
Xiaoxu Ge,1,* Juan Du,1,* Jiajia Wang,2,* Liuqing Xi,1 Jianfang Gao,2 Peng Zhou,2 Wenfang Peng,1 Shan Huang1,* 1Department of Endocrinology, Tongren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China; 2Hongqiao International Institute of Medicine, Tongren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shan Huang, Department of Endocrinology, Tongren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China, Email hs1147@126.comObjective: A higher dietary intake of live microbes has been shown to be associated with a range of health benefits. We aimed to elucidate the associations between dietary intake of live microbes and the risk of prediabetes.Methods: Adult participants from the 1999– 2018 US National Health and Nutrition Examination Survey were included and categorized into the low, medium, and high live microbe intake groups based on the Sanders classification system. Associations between dietary consumption of live microbes and prevalence of prediabetes were explored using univariate and multivariate logistic regression, stratified analysis, and sensitivity analysis.Results: Among the 28201 participants (mean age 45.83 years, 48.40% men, 32.78% with prediabetes) included, 9761 (31.80%), 12,076 (41.42%) and 6364 (26.78%) were classified into the low, medium, and high dietary live microbe intake groups, respectively. After adjusting for all potential covariates, the odds ratios and 95% confidence intervals for the medium and high dietary live microbe intake groups were 0.868 (0.803– 0.937) and 0.891 (0.807– 0.983), respectively (P for trend = 0.017), with the low dietary live microbes intake group as the reference. This association is robust and not affected by participant’s age, sex, race, poverty–income ratio, education level, hypertension status and estimated glomerular filtration rate.Conclusion: A higher consumption of dietary live microbes was found to be cross-sectionally linked to a lower prevalence of prediabetes in US adults.Keywords: cross-sectional, live microbes, NHANES, prediabetes